Coffee Husk and Coffee Ground as an Adsorbent for the Removal of Lead, Copper and Chromium from Aqueous Solution - Medhanit Tefera Yifira; Mesfin Bibiso Doda; Camerun Kastro Kanido (Pakistan Journal of Analytical & Environmental Chemistry, 2023)
This study aimed to investigate the removal efficiency of coffee husk and coffee ground adsorbents to adsorb lead(II), copper(II), and chromium(VI) from an aqueous solution. Standard lead nitrate, potassium dichromate, and copper chloride solutions were prepared following standard laboratory procedures. The residual metallic ion concentrations were determined using Atomic Absorption Spectrometer (AAS). The experimental parameters such as pH, contact time, adsorbent dosage, agitation speed and initial concentration of selected metal ions were evaluated at different particle size fractions (>200 μm and <200 μm) of adsorbent in aqueous solutions. The results revealed that the best adsorption conditions obtained for the heavy metals removal were pH 5, at a contact time of 60 min, an adsorbent dosage of 0.5 g, an initial concentration of 0.5 mg/L, and 115 rpm agitation speed. At fractions of particle size <200 μm, the removal efficiency of adsorbents coffee husk and coffee ground were found as 94.2% and 96.5%, 97.6% and 97.6%, and 93.5% and 94.46% for lead(II), copper(II) and chromium(VI), respectively. Similarly, at the fractions of particle size >200 µm, the removal efficiency of coffee husk and coffee ground investigated were 93.2% and 96.06%, 97.2% and 83%, and 92.4% and 94.46% for lead(II), copper(II) and chromium(VI), respectively. The obtained results show that coffee husk and coffee ground adsorbents used in this study can serve as excellent bio-sorbent for efficiently removing selected heavy metals from the aqueous solutions.